1994
DOI: 10.1039/c39940002239
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinic acid as a bifunctional reagent in the catalytic bamberger rearrangement of nitrobenzene to para-aminophenol

Abstract: Phosphinic acid is proposed as a simultaneous hydrogen donor and proton source in the Pd/C catalysed transformation of nitrobenzene to para-aminophenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…12 This is of special interest to organic synthesis as well as fine chemical production in batch processes. In general, different compounds can be utilized as hydrogen donors, including phosphinic acid salts, 13 isopropanol, 14 hydrazines, 15 formic acid salts 16 and the azeotropic mixture of formic acid-triethylamine. 17 Depending on the catalyst and conditions, functional groups such as ketones, 18 esters, 19 imines 20 and nitro groups 21,22 have been successfully reduced.…”
mentioning
confidence: 99%
“…12 This is of special interest to organic synthesis as well as fine chemical production in batch processes. In general, different compounds can be utilized as hydrogen donors, including phosphinic acid salts, 13 isopropanol, 14 hydrazines, 15 formic acid salts 16 and the azeotropic mixture of formic acid-triethylamine. 17 Depending on the catalyst and conditions, functional groups such as ketones, 18 esters, 19 imines 20 and nitro groups 21,22 have been successfully reduced.…”
mentioning
confidence: 99%
“…190 The possibility to selectively prepare hydroxylamine was exploited by Sasson in 1994 with the Pd/C catalyzed Bamberger rearrangement of nitrobenzene 174 to para-aminophenol 175. 191 Phosphinic acid acts both as hydrogen donor and strong acid (Scheme 61). Aniline was observed as a by-product as well as bis-(4-amino-phenyl) ether 2% and ortho-aminophenol 1%.…”
Section: Deoxygenation Of Sulfur Compoundsmentioning
confidence: 99%
“…Gao et al [9] used PdCl 2 supported on poly(N-vinyl-pyrrolidone) and sulphuric acid with the same surfactant and reported that the addition of Co(OAc) 2 as a second metal catalyst increases the yield of p-AP. Zoran et al [10] obtained p-AP yield of 47 mol% using Pd(5%)/C and phosphorous acid. Pt(3%)/C was reported to be active with sulphuric acid [11,12].…”
Section: Introductionmentioning
confidence: 98%